2018
DOI: 10.1002/anie.201804365
|View full text |Cite
|
Sign up to set email alerts
|

Amino Acid Assisted Incorporation of Dye Molecules within Calcite Crystals

Abstract: Biomineralisation processes invariably occur in the presence of multiple organic additives, which act in combination to give exceptional control over structures and properties. However, few synthetic studies have investigated the cooperative effects of soluble additives. This work addresses this challenge and focuses on the combined effects of amino acids and coloured dye molecules. The experiments demonstrate that strongly coloured calcite crystals only form in the presence of Brilliant Blue R (BBR) and four … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 41 publications
0
39
0
Order By: Relevance
“…71,72 For this purpose, considerable effort has been made to unravel the mechanisms by which additives become incorporated within calcite single crystals. 24,29,[73][74][75] These studies have demonstrated that occlusion is governed by the binding affinity of the additive to the surface of the growing crystal. Efficient occlusion is achieved when an additive binds strongly enough to binding sites on the crystal surface (i.e., kinks and step edges) such that the residence time on the crystal surface exceeds the time taken for steps to propagate around the particles, but not so strongly that crystal growth is inhibited.…”
Section: Discussionmentioning
confidence: 99%
“…71,72 For this purpose, considerable effort has been made to unravel the mechanisms by which additives become incorporated within calcite single crystals. 24,29,[73][74][75] These studies have demonstrated that occlusion is governed by the binding affinity of the additive to the surface of the growing crystal. Efficient occlusion is achieved when an additive binds strongly enough to binding sites on the crystal surface (i.e., kinks and step edges) such that the residence time on the crystal surface exceeds the time taken for steps to propagate around the particles, but not so strongly that crystal growth is inhibited.…”
Section: Discussionmentioning
confidence: 99%
“…The occlusion of additives ranging from small molecules, 7 , 32 , 53 , 54 to polymers, 34 , 55 , 56 to organic and inorganic nanoparticles, 4 , 5 , 8 , 18 , 22 , 24 , 26 , 28 in single crystals provides a unique strategy for creating new materials with tailor-made properties. However, to fully profit from this approach, it is necessary to control the composition and structure of these nanocomposites.…”
Section: Discussionmentioning
confidence: 99%
“…Techniques such as confocal fluorescence microscopy or optical microscopy can provide information about the average distribution of fluorescent or colored additives within a crystal, but the resolution is frequently insufficient to identify the locations of individual nano-sized or molecular additives. 31 , 32 Serial sectioning and successive electron microscopy of samples can be carried out to build a tomographic image, but is both destructive and prone to artefacts. 23 While significant advances have been made in electron tomography, 33 , 34 this technique remains limited in the size of sample that can be studied, such that it is difficult to correlate the locations of the occlusions with the morphology of the host crystal.…”
Section: Introductionmentioning
confidence: 99%
“…the characteristic SEM image of PoLi-bCA/CaCl 2 /CO 2 (i.e. after passing CO 2 ), whereby crystals having average dimensions of ≈ 115 × 103 nm and plausibly resembling rhombohedral calcite crystals could be observed [38][39][40][41][42][43]. A significant polydispersity in size was observed with the largest crystal dimensions being ca.…”
mentioning
confidence: 93%